Plasma Concentration of Immunoglobulin Classes and Subclasses in Children with Autism in the Republic of Macedonia: Retrospective Study - Trajkovski, Vladimir; Ajdinski, Ljupcho; Spiroski, Mirko (My University, 2004)
Aim. To examine plasma concentration of IgA, IgM, IgG classes, and IgG1, IgG2, IgG3, and IgG4 subclasses in children with autism. Methods. Infantile autism was diagnosed by the Diagnostic and Statistical Manual for Mental Disorders (DSM)-IV and the International Classification of Diseases (ICD)-10 criteria. Plasma samples were collected from 35 autistic subjects, and their 21 siblings (biological brothers and sisters)who served as healthy controls. Plasma samples were separated by centrifugation and stored at –20 C until the determination. Plasma immunoglobulin classes (IgM, IgA, IgG) and subclasses (IgG1, IgG2, IgG3, IgG4) were determined using a nephelometer. Results. Plasma concentrations (mean standard deviation) of IgM and IgG in autistic children (1.36 0.31 g/L and 13.14 1.27 g/L, respectively) were significantly higher (p=0.031 and p=0.023, respectively) in comparison with their healthy brothers or sisters (1.20 0.15 g/L and 12.39 0.96 g/L, respectively). Children with autism had significantly higher plasma concentrations of IgG4 (p<0.001) compared to their siblings (healthy brothers or sisters). Plasma concentration of IgA, IgG1, IgG2, and IgG3 were similar in autistic children and their healthy brothers or sisters. Increased plasma concentration of IgG1 was found (p=0.027) in autistic males (8.06 2.40), as compared with their healthy brothers (5.24 4.13 g/L). Plasma concentrations of IgG (14.28 3.66 g/L), and IgG1 (9.41 2.20 g/L) in autistic females were increased (p=0.012 and p=0.021, respectively) in comparison with IgG (11.07 2.07) and IgG1 (6.37 3.38g/L) in their healthy sisters. Conclusion. Children with autism have increased plasma concentration of immunoglobulines. Increased immunoglobulines in children with autism could be a result of impaired development of the immune system, and/or genetic factors connected with defense mechanism in these children.
Keywords: autistic disorder; immunoglobulin isotypes; Macedonia (Republic)